The outcome of fungal infections in a Burn Intensive Care Unit: a study of 172 patients - Diogo Francisco Tomaz (2019)
Background: Burned patients are a special fragile population in which infections are a leading cause of dead and morbidity. Fungal infections have become increasingly prevalent in Intensive Care Units (ICU) and burn ICUs. Management of fungal colonization and infection still constitutes a challenge for clinicians. Aim: characterize the population of burn patients with fungal infections admitted in our Burn ICU. Methods: a retrospective cross-sectional study of all patients admitted to a Burn ICU between 2013 and 2015. 172 patients were included and characterized regarding age, gender, date of admission and exit, type of burn, type of exit, TBSA and presence of inhalation injury. Presence of fungal infection, causative pathogen and site of sampling were also registered. Statistical analysis centered around the presence of fungal infection was performed using IBM SPSS Statistics. Results: 172 patients were included, 38 (22,1%) had a fungal infection and from this 8 (21,1%) died. Patients with fungal infection stayed more days than those without infection. However, this tendency didn't reach statistical significance when patients that died on ICU where excluded. No relations were found when comparing fungal infection with TBSA, burn aetiology, inhalation injury or mortality. Conclusion: fungal infection are a major cause of morbidity and mortality despite of TBSA, burn type or presence of inhalation injury. Efforts should be made to improve management of fungal infections, especially on burn patients and other critically ill groups.